Pengembangan Perangkat Pembelajaran Dalam jaringan Pada Mata Kuliah Struktur Aljabar - Damianus D. Samo; Ofirenty E Nubatonis (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2021)
This study aims to develop online learning tools in the Algebra Structure course. This research is a development using the Kemp model. The learning tools produced in this study are RPS, RTS, teaching materials, learning videos and learning outcomes tests. The results of the validation and testing of the learning tools show that learning tools are valid, practical and effective. The average validator's assessment of the RPS, RTS, Teaching Materials, Learning Videos and Tests Learning outcomes are 3.72, 3.76, 3.76, and 3.72 with good criteria. The average value of observations by observer 1, observer 2 and observer 3 is 4.00, 4.06, and 4.12, with good categories. The results of student responses showed that 93.482% of students satisfied with the teaching component, 84.09% of students satisfied with the novelty of the learning component, 94.87% interest in participating in further learning, 88.88% expressed satisfaction with language clarity, 91.42% satisfied with the appearance of the material teaching and learning videos. The validation of the questions showed that there were 3 items with high validity, and there were 6 items with sufficient validity. Furthermore, the test reliability coefficient = 0.79 which indicates that the learning outcomes test has high reliability and is used without revision. Thus, the validation and testing of the device shows that student activities are effective, lecturers' ability to manage learning is good, student responses are positive and test results are valid and reliable.